JENIS KUPU-KUPU (RHOPALOCERA) DI KAWASAN KOMPLEK PEMDA PASIR PENGARAIAN KABUPATEN ROKAN HULU RIAU - Handayani, Lita Dwi; Yolanda, Rofiza; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about butterflies (Rhopalocera) in complex of Local Government Region Pasir Pengaraian Rokan HuluRiau has been conduafed in Desember 2014 to Januari 2015 with a survey method with a random samplingtechniques. Samples were collected by using insect net in complex area. Result showed 7 families, 10 generaand 10 spesies of butterflies were found, they were Acraea violae, Amathusia phidippus, Ideopsis vulgaris,Junonia orithya, Neptis hylas, Papilio polytes, Appias libythea, Catopsilia scylla, Elymnias hypermnestra danMelanitis leda.